Future Changes of Summer Heat Waves Over Urban Agglomerations in Eastern China Under 1.5°C and 2.0°C Global Warming - Ma, Hongyun; Wang, Ying; Lin, Zhaohui (Frontiers in Earth Science, 2022)
Extreme hot events have increased evidently under global warming, particularly in the urban areas. This study aims to explore the detailed features of future changes in summer heat waves (HWs) over three major urban agglomerations (Beijing Tianjin Hebei, BTH; Yangtze River Delta, YRD; Pearl River Delta, PRD) in eastern China under 1.5℃ and 2.0℃ warming scenario by using the Weather Research and Forecasting model (WRF) with the updated land cover data for China (ChinaLC), which is also coupled with urban canopy model. Based on the future projection results from Community Earth System Model (CESM) under the Representative Concentration Pathway (RCP) 4.5, dynamic downscaling with high-resolution WRF has been performed to project the future changes in frequency, duration and intensity of summer HWs in urban agglomerations under 1.5°C and 2.0°C warming scenarios respectively. Compared with the historical period, it’s found that both the summer HWs indices and the HWs affected areas all increase significantly under 1.5°C and 2.0°C warming scenarios. The increasing rates of the three HWs indices are above 50% under 1.5°C warming situation, and 70% for 2.0°C warming scenario, with the increasing rate of HWs intensity even exceeding 200%. It is noted that an additional 0.5°C warming from 1.5°C to 2.0°C can produce much larger impact on the future HWs changes in YRD, with the HWs intensity increased by 75.5% from 1.5°C to 2.0°C warming scenarios. It’s further found that the changes of HWs indices in urban area is much higher than that of non-urban areas under 1.5°C and 2.0°C warming, indicating that the urban areas will face higher risk of heat-related illness or environments than suburban or rural areas in the future. Our results can provide further scientific support for the mitigation and adaption strategy for the future HWs risk in mega-cities.